0166 'Ebola sim' – an in-situ simulation to test standard operating procedures (SOPS) for a high risk patient pathway. (2nd November 2015) - Brown, Annemarie; Schofield, Louise; Walker, Jonathan; Marinas, Joselito; Goulding, Jeff; Murphy, Mark; Shanahan, Toni; Parr, Tim; Beeching, Nicholas; Beadsworth, Michael; Burke, Andrew
Abstract : Background: Ebola virus disease (EVD) causes severe illness in humans; the recent outbreak in West Africa has been confirmed as the largest in history. In July 2014 the regional centre for Infectious diseases at the Royal Liverpool University Hospital began discussions to review the processes for receiving potential EVD patients. Multidisciplinary meetings were held and a draft 'Standard Operating Procedure' (SOP) was developed. We recognised the potential for unidentified flaws in our SOP, so decided to organise an 'in-situ' simulation to test the SOP, whilst providing staff an opportunity to practice. Methodology: In October 2014 clinicians, clinical educators and managers from the Royal Liverpool Hospital partnered with the Centre for Simulation and Patient Safety to run a large scale 'in-situ' simulation. This involved teams from the Emergency Department, Infectious Diseases and Critical Care, alongside personnel from laboratories, infection control and security. The simulation started within the Emergency Department where a simulated patient self-presented with apparent minor symptoms, but deteriorated quickly and required rapid assessment by specialist teams and transfer to the inpatient bed base. Following the simulation we conducted a debrief involving all staff. Results: Directly observing the simulation and subsequent debriefing identified these areas for improvement: Isolation process Personal protective equipment Communication Time to transfer Safe patient transfer Decontamination Consequently the SOP was revised and additional SOPs produced. The PPE was adjusted and training enhanced. Conclusions: This was the first time SOPs were developed for a complete patient pathway in our Trust. Simulation was utilised due to the complex processes and potential risk to staff and public. The simulation revealed unanticipated gaps in our SOP, resulting in refinement of processes and equipment improvements. In-situ simulation proved very useful in this situation and we would recommend it for testing processes, particularly when they are high risk and complex. References: Centers for Disease Control and Prevention. Ebola (Ebola Virus Disease). 2014. [Online]. [Accessed 12 th February 2015]. Available from: http://www.cdc.gov/vhf/ebola/outbreaks/2014-west-africa/ Moore LSP, et al . Ebola and other viral haemorrhagic fevers: a local operational approach. Br J Hosp Med. 2014;75(9):515–522 Public Health England. Ebola Virus Disease : clinical management and guidance . 2014. [Online]. [Accessed 12 th February 2015]. Available from: http://www.gov.uk/government/collections/ebola-virus-disease-clinical-management-and-guidance World Health Organization. Ebola. 2014. [Online]. [Accessed 12 th February 2015]. Available from: http://www.apps.who.int/ebola/ebola-situation-reports